2019
DOI: 10.1186/s13021-019-0119-7
|View full text |Cite
|
Sign up to set email alerts
|

GHG mitigation in Agriculture, Forestry and Other Land Use (AFOLU) sector in Thailand

Abstract: Background: The Agriculture, Forestry and Other Land Use (AFOLU) sector is responsible for almost a quarter of the global Greenhouse gases (GHG) emissions. The emissions associated with AFOLU activities are projected to increase in the future. The agriculture sector in Thailand accounted for 21.9% of the country's net GHG emissions in 2013. This study aims to estimate the GHG emissions in the AFOLU sector and mitigation potential at various carbon prices during 2015-2050. This study uses an AFOLU bottom-up (AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The AFOLU sector has a large potential to mitigate GHG emissions and to sequester carbon in soils. To realize these potentials, we need to adopt improved technology in the farming system (Malla et al 2005;Kahrl et al 2010;Hasegawa and Matsuoka 2015;Pradhan, Chaichaloempreecha, and Limmeechokchai 2019); better management of inputs such as water, energy, and fertilizer (Zhang et al 2013); improved irrigation methods (Wang et al 2012); better livestock management (Mottet et al 2017;Enahoro et al 2019); and better institutional arrangements ). In the agriculture sector, livestock manure and enteric fermentation represent about 32% of emissions, and rice cultivation produces 8% of global anthropogenic emissions (UNEP 2021b).…”
Section: Mitigation Potential In the Afolu Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…The AFOLU sector has a large potential to mitigate GHG emissions and to sequester carbon in soils. To realize these potentials, we need to adopt improved technology in the farming system (Malla et al 2005;Kahrl et al 2010;Hasegawa and Matsuoka 2015;Pradhan, Chaichaloempreecha, and Limmeechokchai 2019); better management of inputs such as water, energy, and fertilizer (Zhang et al 2013); improved irrigation methods (Wang et al 2012); better livestock management (Mottet et al 2017;Enahoro et al 2019); and better institutional arrangements ). In the agriculture sector, livestock manure and enteric fermentation represent about 32% of emissions, and rice cultivation produces 8% of global anthropogenic emissions (UNEP 2021b).…”
Section: Mitigation Potential In the Afolu Sectormentioning
confidence: 99%
“…More importantly, the global food demand scenarios show a strong increase in animalbased products, primarily in developing countries (Bodirsky et al 2015). Accordingly, there is a need to assess multiple factors, including demand, supply, and other institutional factors, while transforming the AFOLU sector into a low-emissions development pathway (Sutton, Erisman, and Oenama 2007;Smith et al 2013;Pradhan et al 2017;Pradhan, Chaichaloempreecha, and Limmeechokchai 2019;Zeng et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Taking agricultural practices in the greenhouse gas balance faces uncertainty sources. Pradhan and Limmeechokchai [27] reported that the GHG emission from Thailand agricultural sector in 2015 was estimated to be 45. These agricultural GHGs emissions originate from soil management, enteric fermentation, energy use, and manure management [28].…”
Section: Afolu and Ghg Emissionsmentioning
confidence: 99%
“…More importantly, the global food demand scenarios show a strong increase in animal-based products, primarily in developing countries (Bodirsky et al 2015). Accordingly, there is a need to assess multiple factors, including demand, supply, and other institutional factors, while transforming the AFOLU sector into a low-emissions development pathway (Sutton, Erisman, and Oenama 2007;Smith et al 2013;Pradhan et al 2017Pradhan et al , 2019Zeng et al 2020).…”
Section: Introductionmentioning
confidence: 99%